2013
DOI: 10.1117/1.jmm.12.2.023012
|View full text |Cite
|
Sign up to set email alerts
|

MOEMS tunable microlens made of aluminum nitride membranes

Abstract: We present tunable lenses based on aluminum nitride membranes. The achievable tuning range in the refractive power is 0 to 25 dpt with an external pressure load of <= 20 kPa. The lenses are manufactured using MOEMS technology. For 500-nm-thick membranes with a diameter of 3 mm, a spherical deflection profile is found. The system provides good long-term stability showing no creep or hysteresis. A model for the refractive power versus applied pressure is derived and validated experimentally. Based on this model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…If the energy is beyond a certain threshold, the layer is strongly (0 0 2) oriented and the way of ion bombardment does not seem to be important. Furthermore, in [29] it is shown that the nitrogen content in the plasma can be varied in a wide range without losing the nanocrystalline columnar structure of the AlN film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the energy is beyond a certain threshold, the layer is strongly (0 0 2) oriented and the way of ion bombardment does not seem to be important. Furthermore, in [29] it is shown that the nitrogen content in the plasma can be varied in a wide range without losing the nanocrystalline columnar structure of the AlN film.…”
Section: Resultsmentioning
confidence: 99%
“…Die piezoelektrische Aktivität sowie die CMOS Kompatibilität des Materials qualifizieren es für den Einsatz in den Bereichen der Hochfrequenz-MEMS [1] und des "energy harvesting" [2]. Resultierend aus der Nanokristallinität gesputterter AlN-Schichten sind diese mechanisch sehr stabil und da das Material im sichtbaren optischen Bereich transparent ist, können für MOEMS Applikationen mit freitragenden AlN-Strukturen sowohl Linsen [3] als auch Federn [4] nen Balken, ergibt sich der durchschnittliche Stressgradient in der Schicht vor der Freistellung aus folgender Beziehung [11]: [12]. Der intrinsische Stress der Nukleationszone und die mit der Schichtdicke steigende Zugspannung muss folglich mit einer quantitativ äquivalenten, aber invers gerichteten Schichtspannung kompensiert werden.…”
Section: Einführungunclassified
“…Since a 0 3 , β 0 3 and f 0 1 stay constant over the zoom range, we can use (8) to calculate β 0 2 at any given overall focal length f ′ within the zoom range. We use (5), (6) and (2) to receive the missing values of e 0 1 and f 0 2 :…”
Section: Geometrical Relationsmentioning
confidence: 99%
“…Tuneable lenses offer the possibility of changing their focal length without elements moving along the optical axis (e.g. [2] [3] [4] [5]). Therefore, no additional installation space is needed to allow for such a longitudinal movement.…”
Section: Introductionmentioning
confidence: 99%
“…They are of fundamental importance in the realising of novel beam-shaping and -guiding concepts for ultra-compact and powerful optical units for micro-and nanostructuring, which will be integrated into the NPMM in the framework of our research work. Innovative microtechnical methods and procedures can be combined to build efficient active optical modules which will offer high potential for future applications [69][70][71].…”
Section: Future Workmentioning
confidence: 99%